(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article provides brief information about plants growing on the northern coast of Chatyr-Kul Lake. A list of species found there has been compiled. The characteristic of the ornamental plant found here - Pulsatilla campanella Fisch. ex Regel et Tiling. - is given.